2005
DOI: 10.1111/j.1399-5618.2005.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in bipolar disorder: retrospective data from the first 500 STEP‐BD participants

Abstract: Potentially important gender differences in certain illness characteristics were found in our study; however, in contrast to other reports, we did not find higher rates of lifetime depressive episodes or rapid cycling in women. Although our study is limited by its retrospective study design, its results are strengthened by our large sample size and use of structured interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
85
2
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 19 publications
12
85
2
8
Order By: Relevance
“…Bipolar women (both I and II) are nearly twice as likely to have PTSD compared to bipolar men (20.9% vs. 10.6% in the STEP-BD study) [41], which is similar to the general population [14].…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 94%
“…Bipolar women (both I and II) are nearly twice as likely to have PTSD compared to bipolar men (20.9% vs. 10.6% in the STEP-BD study) [41], which is similar to the general population [14].…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 94%
“…This was done in order to examine the unique contribution of primary anxiety disorders to variance in BD. Analyses were conducted separately for males and females owing to the known gender differences in comorbidity in BD (Hendrik et al, 2000;Baldassano et al, 2005). Moreover, a preliminary logistic regression analysis confirmed that there was a significant interaction between gender and youth-onset anxiety as it relates to predicting BD (χ2=6.9, df=1, p=0.009).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It might be absent during periods of mania (Fogarty et al 1994 ). Bulimia nervosa (BN) is seen in 1.4-7.5 % of BD patients (Baldassano et al 2005 ;McElroy et al 2001McElroy et al , 2011Pini et al 1999 ;Strakowski et al 1992Strakowski et al , 1993Vieta et al 2001 ;Seixas et al 2012 ;Fornaro et al 2010 ) and up to 7-12 % in bipolar females (Baldassano et al 2005 ;Strakowski et al 1992 ;Schuckit et al 1996 ). Reversely, BN patients are at a 4.5 times higher risk to also suffer from BD (Lunde et al 2009 ).…”
Section: Comorbid Eating Disordersmentioning
confidence: 96%